How does match status affects the passing sequences of top-level European soccer teams? - Paixao, P.; Sampaio, J.; Almeida, C. H.; Duarte, R. (International Journal of Performance Analysis in Sport, 2015)
The purpose of this study was to identify the effect of match status (winning, losing or drawing) on the length of passing sequences of top-level soccer teams. A total of 20 matches of the knockout phase of the 2008-2009 UEFA Champions League were analysed. The sample consisted of 222 passing sequences leading to shooting opportunities performed by the four semi-finalists teams (FC Barcelona, Manchester United FC, Chelsea FC and Arsenal FC). These passing sequences were selected to reflect how each team tended to break the balance with the opposing teams to reach the goal (symmetry-breaking process). The passing sequences were measured by the number of passes performed until the shot and their respective durations, according to the match status. Results revealed that teams used preferentially long passing sequences when they were losing or drawing, and short passing sequences when they were winning. Besides, these top-level European teams tended to differently adapt the length of their passing sequences according to the evolving score-line, which suggests the existence of a team's signature of play.